Um estudo sobre os obstáculos na eliciação de requisitos de software - Jasper, Bruce Deon (2014)
Over the decades countless methods and tools have been developed aiming to solve the observed problems of software engineering . Because of its recognized importance, the area of requirements engineering has received increasing attention from researchers. Research demonstrates the importance of elicitating and managing software requirements properly and the impacts of this step in IT projects. Best Practices and Success Factors are studied seeking scientific developments and successes in projects undertaken in several areas. However, there are still many unsolved problems in the implementation of activities in this area, mainly in software requirements elicitation. This research sought to understand the obstacles in requirements engineering and contributed to present how formal methods can help, especially goal-oriented methods, an approach that allows elicitating and reasoning about technical requirements and relate them to business goals of stakeholders. In conjunction with traditional methods, this approach can serve to resolve some of the problems presented. As suggestions for further research were recommended the practical application of goal-oriented requirements engineering approaches in software requirements elicitation, among other steps of the development’s cycle, presenting real case studies, performing research directed to show advantages and drawbacks and successful approaches to goal-oriented requirements engineering and execution of studies oriented to building a modeling language that unifies the various existing methodologies, which should facilitate their learning and application by requirements engineers.